Immunization Status of Children Admitted With Measles in a Tertiary Care Hospital - Haider, Aqsa; Humayun, Kehkashan; Moiz, Saima; Ali, Ramsha; Mujeeb, Hira; Ali, Fatima (Biological and Clinical Sciences Research Journal, 2025)
Measles continues to pose a pervasive threat in pediatric healthcare, as it not only has a high rate of transmissibility but also has the potential to lead to severe complications such as pneumonia and encephalitis. Objective: To determine the immunization status of children presenting with measles at a tertiary care hospital. Methods: This Cross-Sectional study design was conducted at the Dept of Pediatrics – Patel Hospital, Karachi, during July 2024 to December 2024. Ethical approval was secured from the Institutional Review Board of the designated tertiary care hospital before data collection began. Pediatric patients admitted with measles were identified and enrolled as study participants after obtaining informed consent from their guardians or parents. Data were gathered using a structured questionnaire designed to capture sociodemographic details, disease history, clinical symptoms, and immunization status. Results: Data were collected from 261 children with a majority being male (59.77%). The mean age was 4.6 years (±2.3). Socioeconomic distribution showed that most participants belonged to low-income families (65%), while middle-income (22%) and high-income (13%) families had lower representation. Regarding parental education, 58% of parents had no formal education, 27% had primary education, and only 15% had secondary or higher education, highlighting educational disparities among the participants' families. Conclusion: It is concluded that immunization plays a critical role in preventing measles and reducing its complications, with fully vaccinated children experiencing significantly lower rates of severe outcomes compared to unvaccinated ones.